A randomised controlled trial of peri‐operative lidocaine infusions for open radical prostatectomy1. (8th January 2016) - Weinberg, L.; Rachbuch, C.; Ting, S.; Howard, W.; Yeomans, M.; Gordon, I.; McNicol, L.; James, K.; Story, D.; Christophi, C.
Summary: We allocated 76 men scheduled for radical retropubic prostatectomy to peri‐operative lidocaine 2% or saline 0.9%: a pre‐operative 0.075 ml.kg −1 intravenous bolus; an intra‐operative intravenous infusion at 0.075 ml.kg −1 .h −1 ; and 24 hours' postoperative subcutaneous infusion at 0.075 ml.kg −1 .h −1 . Lidocaine reduced the postoperative hospital stay by a mean (95% CI) of 1.3 (0.3–2.4) days, p = 0.017, from a mean (SD) of 4.6 (3.2) days with saline. Lidocaine reduced pain at rest during the first 24 postoperative hours by a mean (95% CI) of 1.8 (0.7–2.9) mm.h −1, p = 0.001. Lidocaine reduced 24‐h morphine consumption by a mean (95% CI) of 13.9 (2.2–25.7) mg, p = 0.021, from a mean (SD) of 52.3 (26.9) mg with saline. There were no differences in other outcomes.